Clarifying the biological significance of the CHK2 K373E somatic mutation discovered in The Cancer Genome Atlas database. Issue 23 (25th October 2016) - Higashiguchi, Masayoshi; Nagatomo, Izumi; Kijima, Takashi; Morimura, Osamu; Miyake, Kotaro; Minami, Toshiyuki; Koyama, Shohei; Hirata, Haruhiko; Iwahori, Kota; Takimoto, Takayuki; Takeda, Yoshito; Kida, Hiroshi; et al.
Abstract : We identified CHK2 K373E as a recurrent mutation in The Cancer Genome Atlas (TCGA) database. In this study, we demonstrate that the K373E mutation disrupts CHK2 autophosphorylation as well as kinase activity, thus leading to impairment of CHK2 functions in suppressing cell proliferation and promoting cell survival after ionizing radiation. We propose that K373E impairs p53‐independent induction of p21 WAF 1/ CIP 1 by CHK2. Our data implicate the K373E mutation of CHK2 in tumorigenesis. Abstract :